Epigenetics and the glucocorticoid receptor: A review of the implications in depression. (30th August 2016) - Farrell, Chloe; O'Keane, Veronica
Abstract: Depression is a serious psychiatric disorder that effects at least 350 million people worldwide today. Dysregulation of the hypothalamic-pituitary-adrenal axis (HPAA) is a robust finding in the pathophysiology of depression. This dysregulation is hypothesized to result from altered central glucocorticoid receptor (GR) levels and/or function as a consequence of chronic glucocorticoid (GC) release, leading to receptor resistance. Pivotal animal and human research to date has identified that early life exposure to prolonged levels of GCs, stress and/or depression, can induce epigenetic modifications at key regions on the GR gene that lead to alterations in GR expression and function. Epigenetics provides an attractive mechanism to explain how ones' genes and environment can interact to produce different disease phenotypes. This review aims to compile the information that has been collected to date and to identify key areas for further investigation. Highlights: Links between ELA, HPAA dysfunction and vulnerability to depression are explored. HPAA dysfunction may be, in part, due to hypermethylation at the GR gene promoter. Another promising epigenetic candidate, demethylation at the FKBP5 gene, is discussed.